2017
DOI: 10.1371/journal.pone.0177277
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carotid artery stenosis and retinal nerve fiber layer thickness. A community-based, observational study

Abstract: PurposeTo examine whether an abnormally thin retinal nerve fiber layer (RNFL) is associated with cerebrovascular insufficiency.DesignCommunity-based study.MethodsThe Asymptomatic Polyvascular Abnormalities in Community Study included Chinese aged 40+ years and without histories of cerebrovascular incidents or coronary heart disease. Using transcranial Doppler and carotid duplex ultrasound examination, we assessed presence and degree of an intracranial arterial stenosis (ICAS) and extracranial carotid arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
(25 reference statements)
1
14
1
1
Order By: Relevance
“…also failed to find a significantly reduced RNFL thickness in patients with CAS 7 , a community-based study recently published by Wang et al . does describe reduced RNFL thicknesses in patients with CAS 4 . In functional tests, Kofoed et al .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…also failed to find a significantly reduced RNFL thickness in patients with CAS 7 , a community-based study recently published by Wang et al . does describe reduced RNFL thicknesses in patients with CAS 4 . In functional tests, Kofoed et al .…”
Section: Discussionmentioning
confidence: 89%
“…Management of vascular risk factors, antiplatelet therapy and different surgical procedures (carotid endarterectomy, carotid angioplasty and stenting) are therapeutic options available for the management of carotid artery stenosis. Detection of stenosis of the carotid artery is therefore especially important in neurologically asymptomatic patients 2 – 4 . In current guidelines, the degree of stenosis is an important surrogate measure for stroke risk and indication for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous SD-OCT studies have reported a reduction of the RNFL in cerebrovascular disorders like asymptomatic internal carotid artery stenosis [29] and moyamoya angiopathy [11]. But so far, to our knowledge there is only very little data on SD-OCT and mfVEP changes in microangiopathic ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 94%
“…The previous studies also showed elevated plasma endothelin-1 was associated retinal vein occlusions, anterior ischemic optic neuropathy, and glaucoma ( Iannaccone et al, 1998 ; Flammer et al, 2001 ; Li et al, 2016 ). And the higher degree of carotid arterial stenosis contributed to the thinner RNFL thickness ( Wang et al, 2017 ). However, at present, the study of nailfold microcirculation in ocular diseases is limited.…”
Section: Discussionmentioning
confidence: 99%